Detection of animal fat contaminations in sunflower oil by differential scanning calorimetry - Marikkar, Mohammed Nazrim; Dzulkifly, M.H.; Nor Nadiha, M.Z.; Che Man, Y.B. (Taylor and Francis, 2012)
In this study, the use of differential scanning calorimetric (DSC) heating thermograms was investigated to detect the presence of lard (LD), beef tallow (BT), and chicken fat (CF) as contaminants in sunflower oil. Sunflower oil samples spiked separately with LD, BT, and CF in levels ranging from 1 to 20% (w/w) were analyzed using high performance liquid chromatography (HPLC) to get triacyl-glycerol (TAG) profiles and DSC to obtain their heating profiles. The results showed that below 20% (w/w) level of contamination, both LD and BT in sunflower oil can be detected using characteristic contaminant peaks appearing in the higher temperature region (0 - 50°C) of DSC curve. However, CF contamination in sunflower oil did not show any characteristic peaks in this region, but caused changes only in the exiting thermal transitions in the low temperature region of the DSC curve. Based on the characteristic differences in the peak size, shape and position, it was also possible to make distinction between LD and BT contaminations in sunflower oil.